1984
DOI: 10.1016/s0266-7681(84)80017-0
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Radio-Ulnar Synostosis

Abstract: Thirty-three patients with congenital radio-ulnar synostosis were examined. There was one familial predisposition. Chromosomal patterns were examined in seventeen patients and were normal. Bone maturation appeared normal. The radial deviation angle, in the patients whose distal radial epiphysis had closed, was elevated (Madelung's deformity). However, in the patients whose distal epiphysis maturation score was 8, it was not elevated. On the other hand, elongation of the ulna (plus variant) and/or dorsal disloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 6 publications
0
31
0
2
Order By: Relevance
“…2,4,10 The deformity results from a failure of longitudinal segmentation. 2,4,10 The deformity results from a failure of longitudinal segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,10 The deformity results from a failure of longitudinal segmentation. 2,4,10 The deformity results from a failure of longitudinal segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the palaeopathological and clinical literature illustrates that CULS may also include additional anomalies affecting the upper extremity. The types and severity of malformations vary but may include radial ray defects (e.g., radial hypoplasia to radial aplasia; Madelung's deformity; congenital dislocation of the hip(s); clubfoot; underdeveloped skeletal structures of the forearm; wrist, and/or hand; synostosis of the fibula and tibia; syndactyly; microcephaly; polydactyly; William's syndrome; dwarfism; and oligodactyly, craniosynostosis, and mandibulofacial dysostoses; Mital, ; Schinzel, ; Simmons, Southmayd, & Riseborough, ; Miura, Nakaruma, & Suzuki, ; Cleary & Omer, ; Pagnan, Gollop, & Lederman, ; Hurst, Baraitser, & Wonke, ; Sachar, Akelman, & Ehrlich, ; Waters & Simmons, ; Winfeld & Otero, ). Furthermore, CULS lacks the presence of bone remodelling, sclerotic bone lesions, and the ossification of connective tissues.…”
Section: Differential Diagnosesmentioning
confidence: 99%
“…Additionally, radiographs reveal normal skeletal structures (i.e., adjoining epiphyses). However, dwarfism; and oligodactyly, craniosynostosis, and mandibulofacial dysostoses; Mital, 1976;Schinzel, 1980;Simmons, Southmayd, & Riseborough, 1983;Miura, Nakaruma, & Suzuki, 1984;Cleary & Omer, 1985;Pagnan, Gollop, & Lederman, 1988;Hurst, Baraitser, & Wonke, 1991;Sachar, Akelman, & Ehrlich, 1994;Waters & Simmons, 1996;Winfeld & Otero, 2016). Furthermore, CULS lacks the presence of bone remodelling, sclerotic bone lesions, and the ossification of connective tissues.…”
Section: Post-traumatic Synostosismentioning
confidence: 99%
“…Derotational osteotomy at the site of synostosis or the diaphysis of the radius and ulna in order to fix the forearm in neutral or mild pronation is currently the accepted treatment for synostosis. 2,8,11 Most efforts to separate the synostosis and obtain rotation of the forearm have ended in failure. Yabe 12 released the synostosis and interposed the anconeus muscle to preserve the separation of the radius and ulna.…”
mentioning
confidence: 99%
“…Yabe 12 released the synostosis and interposed the anconeus muscle to preserve the separation of the radius and ulna. Miura et al 8 performed Yabe's procedure and reported that all 8 cases resulted in recurrence of the synostosis. Ikegami et al 4 reported that 5 of 7 cases achieved forearm rotation after Yabe's procedure.…”
mentioning
confidence: 99%